2022
DOI: 10.3390/ijerph192416606
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Iron Deficiency Exhibited in Internationally Competitive, Non-Professional Female Endurance Athletes—A Case Study

Abstract: Background: While iron deficiency is commonly discussed in populations of professional female athletes, less is known about highly trained, sub-elite female athletes (e.g., those winning international age-group competitions) who generally have less access to medical and allied health support. Methods: Thirteen non-professional highly trained female endurance athletes provided training diaries and completed a blood test, where iron markers of haemoglobin (Hb), haematocrit (Hct), C-reactive protein (Crp), serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Iron deficiency anemia (IDA) is frequently observed among endurance athletes and even a low ferritin level attenuates endurance due to premature fatigue. In highly trained, subelite female endurance athletes, almost half were iron deficient (ID) with serum ferritin <30 ng·mL −1 (17). After 1 month of endurance training, plasma levels of iron and ferritin were significantly decreased in Navy sailors (18).…”
Section: Components Of Nutritionmentioning
confidence: 99%
“…Iron deficiency anemia (IDA) is frequently observed among endurance athletes and even a low ferritin level attenuates endurance due to premature fatigue. In highly trained, subelite female endurance athletes, almost half were iron deficient (ID) with serum ferritin <30 ng·mL −1 (17). After 1 month of endurance training, plasma levels of iron and ferritin were significantly decreased in Navy sailors (18).…”
Section: Components Of Nutritionmentioning
confidence: 99%
“…Finally, many studies reported iron deficiency as a frequent condition in both professional [64,65] and non-professional [66] athletes, especially female ones. If left untreated, iron deficiency can develop into anemia.…”
Section: Anemic States Characterized By the Increase In Hepcidin Releasementioning
confidence: 99%
“…Within athlete populations, it is commonly reported that the prevalence of iron deficiency (anaemia (IDA) and non-anaemia (IDNA)) is 15-35 % in females and ~3-11 % in males [8][9][10]. However, specific athlete cohort studies report > 50 % of a study population can present with compromised iron stores [11,12].…”
Section: Introductionmentioning
confidence: 99%